Answer:
41
Step-by-step explanation:
48-3=45
45-4=41
Answer:
your answer is (4)(-5)(3)
Step-by-step explanation:
HOPE I HELPED!!!!!
PLEASE MARK ME AS BRAINLIEST PLS I WOULD BE HAPPY IF YOU DID!!
Answer:
y = - 4
Step-by-step explanation:
Given
y = 2x + ( - 2) , that is
y = 2x - 2 ← substitute x = - 1
y = 2(- 1) - 2 = - 2 - 2 = - 4
This is confirmed by the point (- 1, - 4 ) on the graph
Answer:
x²/2166784 +y²/2159989 = 1
Step-by-step explanation:
The relationship between the semi-axes and the eccentricity of an ellipse is ...
e = √(1 -b²/a²)
In order to write the desired equation we need to find 'b' from 'e' and 'a'.
__
<h3>semi-minor axis</h3>
Squaring the equation for eccentricity gives ...
e² = 1 -b²/a²
Solving for b², we have ...
b²/a² = 1 -e²
b² = a²(1 -e²)
<h3>ellipse equation</h3>
Using the given values, we find ...
b² = 1472²(1 -0.056²) = 2166784(0.996864) ≈ 2159989
The desired equation is ...
x²/2166784 +y²/2159989 = 1
Answer: A
Step-by-step explanation: Hope this help :D